Ekonomi Sirkular Berbasis Syariah: Solusi untuk Pembangunan Berkelanjutan - Mashadi, Ali Imron (FADZAT: Jurnal Ekonomi Syariah, 2024)
This article explores the integration of circular economy and sharia principles as an innovative solution to achieve sustainable development. Through a systematic literature review, this study analyzes how Islamic values ??can strengthen the implementation of circular economy in achieving the Sustainable Development Goals (SDGs). The results show that sharia-based circular economy offers a holistic and ethical framework to address contemporary environmental and socio-economic challenges. The concept of maqasid sharia provides a strong moral foundation for sustainable economic practices, while Islamic financial instruments such as green sukuk and productive waqf can facilitate the transition to a circular economy. This integration not only supports environmental protection but also ensures social justice and inclusive economic welfare.